A review on interaction of groundwater and surface water. (29th September 2009) - Eslamian, Saeid; Nekoueineghad, Behzad
Interactions between groundwater and surface water play a fundamental role in water resources management. The movement of water between groundwater and surface water should be investigated in view of both quantity and quality aspects of water resources. In this paper, an attempt is made to define the primary concepts of this interaction and to illustrate a case study undertaken in Australia.